A 34-year-old male with pain and mobility of upper left lateral incisor tooth - Ahmed, Sageer; Parvin, Chowdhury Afrina; Hossain, Mozammal (Bangabandhu Sheikh Mujib Medical University Journal, 2020)
This article has no abstract. The first 100 words appear below: A 34-year-old male attended with mild pain during mastication and slight mobility on the upper left lateral incisor tooth for 2 months. He gave the history of trauma on the offending tooth 3 years ago and for this he visited to a local dentist 2 weeks ago but did not get any relief after treatment. On clinical examination, the tooth was non vital, tender to percussion with 2 degree mobility, not associated with any swelling and discharge. Pre-operative radiograph revealed obliteration of pulp chamber, area of rarefaction associated near the apex of upper left lateral incisor tooth, cervical radiolucency indicating the loss of periodontal structures and about 5 mm separated fragment of instrument in the coronal third of the root canal.